STUDENTS’ PERCEPTIONS TOWARDS THE IMPLEMENTATION OF MALL IN ENGLISH LEARNING: A CASE IN SENIOR HIGH SCHOOL - Adhitias Dewi Helda Ningrum; Farouk Imam Arrasyid (ELLTER Journal, 2021)
Abstract: In this 21st century era therm of Mobile Assisted Language Learning becomes a part of teaching and learning activity in English Education. Mobile Assisted Language learning offers various benefits to both teachers and students. Though, it offers various benefits, in practice it is still debatable thing. Thus, this research was tried to investigate students’ perception towards the implementation of MALL in their learning process. The research was taken at Senior High School in SMAN 1 Dukupuntang. This current study use descriptive qualitative method, and the data were collected through open-ended questionnaires and interview to get the relevant data. The present research shows that students tend to have good perception on the implementation of MALL in English Learning. In using MALL, students use several applications and software to help them study about English Language both inside and outside the classroom. By using MALL, students feel that it was more enjoyable and able to get the information quickly. This research also shows the challenges that faced by the students when they use MALL in English Learning activity. In conclusion, this research shows that students’ have positive perception towards MALL in English Learning.